2023
DOI: 10.1039/d2cc06068j
|View full text |Cite
|
Sign up to set email alerts
|

Cu-catalyzed cascade difluoroalkylation/5-endocyclization/β-fluorine cleavage of ynones

Abstract: A copper-catalyzed, redox-neutral cascade difluoroalkylation/5-endo annulation/β-fluorine cleavage of ynones is developed, providing a direct and stereoselective method to access synthetically important α-monofluoroalkenyl cyclopentanones. Mechanistic studies suggest an unprecedented CuII-assisted β-fluorine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…under similar copper-catalyzed conditions yielded a distinct outcome. 42 The products were identified as α-monofluoroalkenyl cyclopentanones 28 (Scheme 15, black cycle) that were formed via reductive β-fluorine elimination, rather than α-difluoroalkyl cyclopentenones that were produced via oxidative deprotonation as depicted in Scheme 14. Such a difference indicated that an in situ -generated reductant was involved.…”
Section: Intramolecular C(sp3)–h Functionalizationmentioning
confidence: 99%
“…under similar copper-catalyzed conditions yielded a distinct outcome. 42 The products were identified as α-monofluoroalkenyl cyclopentanones 28 (Scheme 15, black cycle) that were formed via reductive β-fluorine elimination, rather than α-difluoroalkyl cyclopentenones that were produced via oxidative deprotonation as depicted in Scheme 14. Such a difference indicated that an in situ -generated reductant was involved.…”
Section: Intramolecular C(sp3)–h Functionalizationmentioning
confidence: 99%
“…The 5‐endo‐trig radical cyclization provides a straightforward approach to five‐membered rings, including cyclopentanes, cyclopentenones and related compounds [9] . In continuation of our research interests in exploring synthetically useful 5‐endo annulations, [9g–k] we envisioned that DFCPs might be constructed via a cascade difluoroalkylation/1,5‐hydrogen atom transfer (1,5‐HAT)/5‐endo cyclization/oxidative deprotonation of ynones (Scheme 1d). Such a reaction is realized under the visible light photoredox conditions, [10] thus providing a very mild and expedient protocol for the assembly of DFCPs that are challenging to access otherwise.…”
Section: Introductionmentioning
confidence: 99%